2013
DOI: 10.1103/physrevlett.111.053601
|View full text |Cite
|
Sign up to set email alerts
|

Giant Cross–Kerr Effect for Propagating Microwaves Induced by an Artificial Atom

Abstract: We investigate the effective interaction between two microwave fields, mediated by a transmon-type superconducting artificial atom which is strongly coupled to a coplanar transmission line. The interaction between the fields and atom produces an effective cross-Kerr coupling. We demonstrate average cross-Kerr phase shifts of up to 20 degrees per photon with both coherent microwave fields at the single-photon level. Our results provide an important step toward quantum applications with propagating microwave pho… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

11
211
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 225 publications
(223 citation statements)
references
References 37 publications
11
211
1
Order By: Relevance
“…Fortunately, Xing et al showed that the weak measurement can be applied to amplify the phase shift to the observable value [59]. Current experiment showed that the "giant" cross-Kerr effect with phase shift of 20 degrees per photon has been observed [60].…”
Section: Measuring the Concurrence Of Arbitrary Hyperentangled Statementioning
confidence: 99%
“…Fortunately, Xing et al showed that the weak measurement can be applied to amplify the phase shift to the observable value [59]. Current experiment showed that the "giant" cross-Kerr effect with phase shift of 20 degrees per photon has been observed [60].…”
Section: Measuring the Concurrence Of Arbitrary Hyperentangled Statementioning
confidence: 99%
“…In the absence of a control photon, the system is completely transparent to the probe. A single control photon will sequentially excite the chain of transmons, displacing the state of the probe field [19], which we show can be detected by homodyne measurement of the probe.…”
mentioning
confidence: 99%
“…The effective nonlinear interaction between the control photon and the probe field is realized by N noninteracting artificial atoms (transmon devices [18]) coupled to the transmission line. Transmons are particularly attractive in light of recent work demonstrating strong atom-field coupling in the singlephoton regime in open waveguides [19]. We treat the atoms as anharmonic three-level ladder systems with energy FIG.…”
mentioning
confidence: 99%
“…In the microwave regime the detection of single photons [6][7][8][9][10][11][12][13][14][15] is more challenging, especially nondestructive detection [6,9,14,15]. Here we propose a scheme for nonabsorbing, high-efficiency detection of single itinerant microwave photons via the nonlinearity provided by an artificial superconducting atom, a transmon [16].Previously [15,17], we considered schemes where the signal photon wave packet propagates freely in an open transmission line [11,18] and encounters the lowest transition of a transmon. The cw-probe field couples the first and second excited states of the transmon and is monitored via continuous homodyne detection.…”
mentioning
confidence: 99%
“…Previously [15,17], we considered schemes where the signal photon wave packet propagates freely in an open transmission line [11,18] and encounters the lowest transition of a transmon. The cw-probe field couples the first and second excited states of the transmon and is monitored via continuous homodyne detection.…”
mentioning
confidence: 99%